Comprehensive analysis of the performance of the coaxial heat exchanger with turbulators - Turgut, Emre; Yardimci, Ugurcan (Elsevier France-Editions Scientifiques Medicales Elsevier, 2022)
In this study, effects of semicircular striped turbulators, inserted into inner tube of a coaxial heat exchanger on the heat transfer (Nu), friction factor (f) and thermal performance factor (TPF) are analyzed. Pitch (p), thickness (t), diameter (d), arrangement style (a) and Reynolds number (Re) were chosen as design parameters (control factors). With the determined design parameters, it was observed that Nu and f values increased by 5.43 and 4.71 times, respectively, compared to the empty pipe, and the TPF increased up to the value of 3.72. The design parameters are addressed as; Three analysis methods are applied to the study, namely; (i) Taguchi Experimental Design (TED), (ii) Analysis of Variance (ANOVA) and (iii) Grey Relational Analysis (GRA). With TED, optimum parameter levels that maximize heat transfer and minimize friction factor have been determined. The percentage effects of these parameters on the heat transfer and friction factor were obtained by the second method, ANOVA. As a result of the analyzes, most efficient parameter on Nusselt number is found as Reynolds number (31%), whilst the lest efficient parameter is found as the pitch (1.74%). The arrangement style of the turbulators has the strongest effect (32.94%) and, similarly, to the heat transfer, the pitch has the weakest effect (nearly negligible) on the friction factor. Lastly, the effects of control factors on the heat transfer and pressure loss are evaluated together, by using GRA and so multi performance characteristics are determined. According to this analysis, it was seen that the most effective parameter on the multi performance characteristic was the Reynolds number, and the most ineffective parameter was the thickness.
Keywords: Turbulator; Heat exchanger; Thermal performance; Taguchi method; Grey relational analysis; ANOVA